Regulating the law enforcement of marital rape with regards to the prevalence of child marriage in Malaysia / Muhammad Anas Baharudin, Ahmad Nur Izzuddin Annual, Nurul Izzati Ahmad Nasaruddin - Baharudin, Muhammad Anas; Anual, Ahmad Nur Izzuddin; Ahmad Nasaruddin, Nurul Izzati (2014)
This research paper is conducted for better understanding in regulating the marital rape enforcement with regards to the prevalence of child marriage in Malaysia. The project paper is divided into several parts, namely the reason and purpose of marital rape in order to have a better understanding for the purpose of the enforcement, the conceptual and theoretical framework of the research project in depth such as the meaning of rape, child rape, marital rape, child marriage, as well as how they are interpreted, applied and developed, emphasizes the law concerns on the child marriage as well as the law required for enforcement of marital rape. It also focuses on the report made by the government and the non-government bodies which concerns on this particular matter, outlines the whole overview of the research by critically answering the research question and underline the objectives of the research paper to enforce the marital rape in order to protect a child who has been involved in a child marriage from being abuse, and recommendation for the enhancement of proper legal procedure of a child marriage. It also made up to increase the awareness of the side effect of marriage at early age towards married child and their families to the societies